2009
DOI: 10.1007/s10802-009-9341-1
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Externalizing and Internalizing Symptoms over Time: The Role of Individual Differences in Patterns of RSA Responding

Abstract: We examined associations between basal respiratory sinus arrhythmia (RSA) in conjunction with RSA regulation with the hypothesis that their interaction would explain unique variability in children's prospective adjustment 2 years later. Participants were 176 children (98 girls; 78 boys) in middle childhood. RSA regulation was assessed through social and problem-solving challenges. Parents reported on children's internalizing and externalizing symptoms. Interactions between RSA baseline and regulation to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
185
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(206 citation statements)
references
References 59 publications
(102 reference statements)
18
185
1
Order By: Relevance
“…Thus, further studies of RSA patterns may be useful for elucidating the mechanisms by which depression risk is transmitted within families. Our finding of elevated depressive symptom trajectories among youth with atypical RSA patterns is in line with reports by other investigators using healthy child samples (Hinnant & El-Sheikh, 2009, 2013). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, further studies of RSA patterns may be useful for elucidating the mechanisms by which depression risk is transmitted within families. Our finding of elevated depressive symptom trajectories among youth with atypical RSA patterns is in line with reports by other investigators using healthy child samples (Hinnant & El-Sheikh, 2009, 2013). …”
Section: Discussionsupporting
confidence: 93%
“…Recent theoretical and empirical work suggests that studying resting RSA and RSA reactivity individually provides an incomplete picture of the relationship between the PNS and adaptive functioning (Del Giudice, Ellis, & Shirtcliff, 2011; El-Sheikh & Erath, 2011; Hinnant & El-Sheikh, 2009, 2013). This notion was raised in Lacey’s (1959) seminal work, which showed that a single index of a physiological system may obscure the extent of interindividual differences.…”
Section: Measuring Pns Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects the emotion dysregulation aspect of externalizing behavior (see Beauchaine et al, 2007;Beauchaine et al, 2009;Beauchaine & Gatzke-Kopp, 2012). In contrast, less RSA withdrawal is found among externalizing samples than controls during attention demanding, executive function, and problem-solving tasks (e.g., Dietrich et al, 2007;Hinnant & El-Sheikh, 2009;Obradović et al, 2010). This likely reflects attentional difficulties among externalizers (see Beauchaine, 2001;Rash & AguirreCamacho, 2012).…”
Section: Emotion Dysregulation and Youth Psychopathologymentioning
confidence: 99%
“…Conversely, low tonic RSA reflects rigidity or a diminished capacity for flexible responsivity (Ode, Hilmert, Zielke, & Robinson, 2010). Low tonic RSA has been associated with a host of emotion-related problems including aggression (Gordis, Feres, Olezeski, Rabkin,& Trickett, 2010;Hinnant & El-Sheik, 2009;Mezzacappa et al, 1997), anxiety (Kawachi, Sparrow, Vokonas, & Weiss, 1995;Watkins et al, 1998;Yeragani et al, 1993), and depression (Carney et al, 1995;Krittayaphong et al, 1997;Licht et al, 2008). Thus, even in the absence of a stressor, tonic HRV can reveal a great deal about an individual's emotional functioning.…”
Section: Tonic and Phasic Hrvmentioning
confidence: 99%